Enhanced antitumor efficacy through microwave ablation combined with a dendritic cell-derived exosome vaccine in hepatocellular carcinoma. (1st January 2020) - Zhong, Xinyu; Zhou, Yan; Cao, Yuting; Ding, Jianmin; Wang, Peng; Luo, Ying; Liu, Hui; Zhu, Zhengyan; Jing, Xiang
Abstract: Aim: To investigate the antitumor efficacy of microwave ablation combined with dendritic cell-derived exosomes (Dex) or dendritic cells (DC) in treating hepatocellular carcinoma using a tumor- bearing mouse model. Methods: We used a bilateral tumor- bearing mouse model treated with MWA, MWA + DC (DC-combined group) or MWA + Dex (Dex-combined group). Following tumor ablation on one side, the tumor volume on the contralateral side was monitored. The proportions of CD8 + (cytotoxic) T cells and regulatory T (Treg) cells in the spleen were analyzed by flow cytometry, and the number of CD8 + T cells and Treg cells in tumor sites was detected by immunohistochemistry. The concentration of interleukin-10 and interferon-γ in plasma was identified using enzyme-linked immunosorbent assay. Results: The combination therapy significantly inhibited tumor growth compared with MWA monotherapy. In addition, the tumor immune microenvironment was significantly improved in HCC mice in the combination therapy groups compared to MWA group demonstrated by an increased number of CD8 + T cells and a decreased number of Treg cells in tumor sites. A lower proportion of Treg cells were observed in the spleen in the combination therapy groups compared to MWA group. Moreover, the concentration of plasma IFN-γ increased, and the concentration of plasma IL-10 decreased in the combination therapy groups compared to the MWA group. However, there was no statistical difference between the Dex-combined group and the DC-combined group in the comparisons mentioned above. Conclusions: Our results provide evidence that MWA combined with Dex can significantly inhibit tumor growth and improve the immune microenvironment compared to MWA alone. Furthermore, the immune-enhancing effect of Dex and DC was equivalent in our combination therapy strategy. Graphical Abstract: